Students’ Perception on The Use of YouTube Video to Improve Learning Motivation at Junior High School - Moh. Iqhfar. Fajar; Aminah; Mashuri; Abd. kamaruddin (IDEAS: Journal on English Language Teaching and Learning, Linguistics and Literature, 2024)
This study aims to explore students' perceptions of using YouTube videos as a medium for learning English, focusing on its impact on learning motivation. The research employs descriptive qualitative methods to analyze YouTube videos as a learning tool. Data were collected through structured and open-ended interviews with 20 ninth-grade students at SMP N 3 Sindue Tobata and questionnaires. The findings indicate that most students are motivated to learn English through YouTube videos. A total of 70% of students agreed that YouTube increased their confidence in using English in daily conversations, while 25% agreed that the ease of accessing English learning materials on YouTube encouraged them to study more frequently. All students agreed that YouTube helps improve their vocabulary and pronunciation and significantly boosts their motivation to learn English through engaging and educational content. However, challenges such as distractions and reliance on stable internet access highlight the need for a structured approach to integrating YouTube into learning. The study concludes that students have a positive perception of YouTube videos as an effective tool to enhance their motivation and English skills.